Technology Upgrading, Learning, and Exports among Manufacturing Firms in a Liberalizing Environment - Mainga, Wise; Lam, Tri D. (European Scientific Journal, ESJ, 2020)
This paper focuses on examining the empirical relationship between technology upgrading, disaggregated skills upgrading variables, and exports among manufacturing firms in the Greater Johannesburg Metropolitan Council (GJMC). The importance of skill development as a determinant of value-added in export basket, and the latter’s subsequent impact on economic development, is widely acknowledged. The analysis of the relationship between disaggregated training variables and exports are rare. The data used in this study comes from the joint World Bank/Greater Johannesburg Metropolitan Council co-ordinated survey of large manufacturing firms, within the Greater Johannesburg Metropolitan Council (GJMC) area. Some of the key findings of the paper are as follows. First, the data analysis supports the perspective that different knowledge accumulation channels (or learning mechanisms) may have differential impact on exports; Imports and exports tend to be complementary, thereby re-enforcing firm-level learning and capability building. Dynamic capability building can take place if exporting activities drives the importation of capital goods. Second, recently introduced product lines had a positive impact on exports, suggesting the importance of frequent product upgrading/product innovations in exploiting competitive and demanding export markets. Third, a lot of training offered to different occupational groups did not seem to have any significant impact on exports. The results raise questions about the quality, content, and focus of employment-based training programs. One major implication of the study findings is that skill upgrading of ‘unskilled production workers’ through inhouse firm-based training is key to ensuring production of quality ‘exportgrade’ output. The importance of frequent product upgrading when targeting demanding export markets suggests the need to have policy objectives that strengthen the National Innovation System.